Optimizing Village-Owned Enterprises Management to Enhance Community Welfare in Modong Village, Sidoarjo Regency - Alfin, Rita (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
This study aims to determine the principles of managing village-owned enterprises to improve people's welfare in the Modong, Sidoarjo Regency village. This study used a qualitative approach with a descriptive research type. The authors used data collection techniques through interviews and observations to obtain the informant data needed in this study. Research shows that the management of BUMDes in Modong Village, Sidoarjo Regency, can be seen from three aspects: 1) Good cooperation between BUMDes managers and the village government can be seen in the form of village budgets allocated to business programs, although the amount is still limited. 2) Good accountability can be seen in administrative reports routinely carried out every year and in business forms such as savings and loans and the provision of iron tents or aisles. 3) Business continuity, in general, has been going well because most Modong Village residents are farmers. Therefore, BUMDes managers hope to get capital assistance in the agricultural sector, such as fertilizers, poisons and seeds, to make it easier for the community to access agrarian materials. The role of BUMDes in Modong Village in developing potential and empowering the community, in general, has been going well. However, there are still some things that need to be improved. The supporting factor is the government's commitment to overcoming poverty and empowering villages through BUMDes, which is reflected in the allocation of funds from village funds, district budgets, provincial budgets, and related ministries. However, the still limited village budget for developing larger businesses is the inhibiting factor.